ï¿¼PROMOTING A RESPECT FOR DIFFERENCE ï¿¼THROUGH LANGUAGE TEACHING - Alistair Welsh (TEFLIN, 2014)
An emphasis on developing studentsâ moral and ethical character is evident in the 2013 National Indonesian Curriculum. In this article, I look at how respect for difference is reflected in the 2013 Indonesian National Curriculum, specifically referring to the second key competency area for senior high school English language. I also draw reference from academic literature that can be linked to this competency area of the English curriculum. Exploring theoretical links from the literature is useful to develop a deeper understanding of the importance of this key competency area. Discussion explores the significance of respect for difference and the important role that English language teachers in Indonesia can play in promoting tolerance. By understanding how culture can be used as a divisive force, we can more readily identify how teachers can develop a respect for difference in their students to help overcome intolerant attitudes that can lead to discrimination.Â